Образы-схемы метафор "жизнь – путь", "жизнь – круг", "жизнь – борьба" в русской прозе В.В. Набокова - Maltseva, Gayane (Acta Polono-Ruthenica, 2021)
The article presents an analysis of the Russian-language prose by V.V. Nabokov, written during the years of emigration, in Berlin, namely, the stories A Guide to Berlin, The Circle and Tyrants Destroyed. The identification of the key image of the text and its schematization are justified by the position of V.V. Nabokov: “I think in images”. The image underlying the texts under study is revealed through associative series (directions of association), which make it possible to define a key textual metaphor – “life is a way”, which in turn includes such metaphors as “life is a circle”, “life is a fighting”. The conditions of the game text complicate the decoding process, require a special reader (for V.V. Nabokov, this is a “re-reader”), a deep analysis of the language material. The author’s proposed method of constructing a matrix model of an idioset allows identifying encoded textual meanings. The non-standard linguistic personality of the writer presents us with special ways of conceptualizing the world. Schematization of the complex philosophy of life allows large amounts of information to be “packed” into an atom of meaning. The reference to precedent texts of different cultures and epochs confirms the universality of the information accumulated in the image. The revealed images are presented graphically, conclusions are drawn about the philosophy of life of V.V. Nabokov: the idea of the duality of being, the opposition of material and spiritual, philistine and poetic, the philosophy ofthe infinity of life processes, repetition and flow. The image becomes a place of maximum concentration of textual meaning.